THE EFFECT OF GOLD PRICE AND RUPIAH EXCHANGE RATE ON THE COMPOSITE STOCK PRICE INDEX ON THE INDONESIA STOCK EXCHANGE - Rabbani, Muhammad Ihsan; Nurhayati, Immas; Yudiana (Universitas Ibn Khaldun Bogor, 2025)
This research aims to examine the influence of gold prices and the rupiah exchange rate on Indonesia's Jakarta Composite Index (JCI). The study applies multiple linear regression analysis, using a t-test to assess the individual impact of each independent variable and an F-test to evaluate their combined effect on the dependent variable. Based on the t-test results, gold price has a significant negative relationship with the JCI, as shown by a significance level of 0.000 and a t-value of -6.912, indicating that higher gold prices tend to suppress the JCI. Conversely, the rupiah exchange rate does not show a significant partial impact on the JCI, with a significance value of 0.277 and a t-value of 1.099. However, the F-test reveals that gold prices and the exchange rate together significantly affect the JCI, with a significance level of 0.000 and an F-value of 87.957, exceeding the critical F-value of 3.16. Thus, it can be inferred that while only gold prices have a notable individual impact, both variables collectively influence the fluctuations in the JCI.